Striatal M4 muscarinic receptors determine the biological rhythm of activity, with a supportive role of M1 muscarinic receptors - Janisova, Katerina; Uhlirova, Monika; Forczek, Sandor; Myslivecek, Jaromir (Frontiers in Pharmacology, 2025)
IntroductionM4 muscarinic receptor (mAChR) knockout changed the female activity biological rhythm parameters. In this study, we focus on the biological rhythms of mAChRs (total + M1 mAChRs), acetylcholinesterase (AChE), and butyrylcholinesterase (BuChE) in M4 mAChR knockout (M4KO) and wild-type (WT) mice in specific brain areas.MethodsFemale mice were sacrificed every 4 hours, brains were removed, mAChRs were determined by autoradiography, and punching was used for the measurement of acetylcholinesterase and butyrylcholinesterase activity. The density of mAChRs was correlated with locomotor activity.ResultsAn ultradian rhythm in total mAChRs was found in the suprachiasmatic nucleus (SCN) (both M4KO and WT). M4KO had a positive correlation between the number of mAChRs and locomotor activity. This rhythm was changed to circadian in WT with a peak in the active phase and to circadian rhythm in M4KO with phase shifts to the inactive/active phase in the intergeniculate leaflet (IgL) (positive correlation in KO), subparaventricular zone (SPVZ) (negative correlation in WT), and posterior hypothalamic area (PHA) (positive correlation in WT). The thalamus (TH) reveals circadian rhythms in WT and M4KO, with a peak in the active phase (no correlation). The striatum (Str), i.e., caudate ncl-putamen (CPu) (decrease in M4KO, positive correlation in both WT and KO) and the motor cortex (MCx) (no correlation), showed circadian rhythms (peak in active phase). Caudate ncl-putamen M1 mAChRs rhythm in WT was circadian, while M4KO animals revealed an ultradian rhythm. Cholinesterases revealed ultradian and circadian rhythms in different areas.DiscussionWe conclude that muscarinic receptor-directed biological rhythm of activity is determined in the striatum (caudate ncl-putamen) as a key structure mainly by M4 mAChRs with a supportive role of M1 mAChRs.